The effect of post-consumer recycled polyethylene (PCRPE) on the properties of polyethylene blends of different densities. (August 2021) - Cecon, Victor S.; Da Silva, Paulo F.; Vorst, Keith L.; Curtzwiler, Greg W.
Highlights: Linear relationships between PCRPE content and polymer properties were determined. Different property trends determined from PCRPE on polymer properties based on PE density. Increased presence of degradation compounds was observed with more PCRPE content. No heavy metal concerns were determined on virgin/recycled polyethylene blends. Abstract: Polyethylene (PE), a versatile polymer present nearly everywhere, poses many challenges as more of it becomes terrestrial and marine waste and used for everything from packaging such as plastic bag production (LDPE) to construction pipes (HDPE). As more companies are required to follow government regulations and consumers' requests to produce more sustainable products, the general interest in PE recycling continues to gain momentum. Several processes have been developed to recycle PE, but current data gaps exist on the impact of adding post-consumer recycled polyethylene (PCRPE) to different virgin feedstocks on final product performance. To better understand this impact, a single source of PCRPE was melt blended with four different virgin PE grades at different concentrations (0, 20, 40, 60, 80, and 100 wt% of PCRPE), and changes in the physical, thermal, and mechanical properties were evaluated. Different trends and behaviors were observed depending on the PE density, however, most properties still followed the Law of Mixtures. For example, low-density PE's mechanical strength improved up to 70% increase in tensile modules and 56% in yield strength. The density was increased by 5%, and no toxic heavy metals (Cd, Cr, Hg, Pb) were found, with less than 4 ppm of Al, Fe, and Ti detected. The insights obtained when mixing polyethylene of different densities with a single recycled grade PE allows plastic manufacturers and recyclers to gain a more comprehensive view of possibilities associated with PCRPE. The results presented herein and previously from our group suggest most physical properties of PCRPE blends follow the Law of Mixtures, enabling the possibility for performance property predictive modeling of different compositions by understanding properties from the virgin and PCR materials alone. The introduction of PCRPE blends also reduces costs by tailoring products to optimal performance and maximum recycled content.